A new species of the genus Thanatus (Araneae: Philodromidae) from Guangxi, China - Wang, Yingnan; Zhang, Feng; Xing, Shuwen (Acta Arachnologica, 2012)
A new species of the genus Thanatus C. L. Koch 1837 is described from Guangxi Zhuang Autonomous Region, China under the name of Thanatus damingus.